2022
DOI: 10.1108/jima-11-2021-0370
|View full text |Cite
|
Sign up to set email alerts
|

Does market performance mediates the nexus between production performance and financial performance in manufacturing companies?

Abstract: Purpose Based on recent government reports, the manufacturing industry is considered one of the most important sectors in Palestine. In this sense, this empirical study aims to investigate the influence of production performance on financial and market performances, assess the influence of market performance on financial performance and test the mediating role of market performance on the relationship between production and financial performances. Design/methodology/approach A convenience sampling method was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
0
0
Order By: Relevance
“…The merger between Human Resource Management (HRM), Strategic Marketing Management, and Corporate Financial Performance has gained significant attention in the The first study, conducted by Cetin, 2010 in Turkey, showed that human resource management has no statistically significant effect on the financial performance of the company. However, marketing management and production management have a significant positive influence on financial performance (Shanak & Abu-Alhaija, 2023). In addition, this study highlights the role of full mediation by production management and partial mediation by marketing management in the relationship between human resource management and financial performance.…”
Section: Literature Reviewmentioning
confidence: 68%
“…The merger between Human Resource Management (HRM), Strategic Marketing Management, and Corporate Financial Performance has gained significant attention in the The first study, conducted by Cetin, 2010 in Turkey, showed that human resource management has no statistically significant effect on the financial performance of the company. However, marketing management and production management have a significant positive influence on financial performance (Shanak & Abu-Alhaija, 2023). In addition, this study highlights the role of full mediation by production management and partial mediation by marketing management in the relationship between human resource management and financial performance.…”
Section: Literature Reviewmentioning
confidence: 68%